Wide Bandgap Semiconductors Fundamental Properties and Modern Photonic and Electronic Devices - Takahashi, Kiyoshi; Yoshikawa, Akihiko; Sandhu, Adarsh; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
This book offers a comprehensive overview of the development, current state and future prospects of wide bandgap semiconductor materials and related optoelectronics devices. It includes an overview of recent developments in III-V nitride semiconductors, SiC, diamond, ZnO, II-VI materials and related devices including AIGaN/GaN FET, UV LDs, white light LEDs, and cold electron emitters. With 901 references, 333 figures and 21 tables, this book will serve as a one-stop source of knowledge on wide bandgap semiconductors and related optoelectronics devices. After reviue of the basic physics of WBGS and the relevance of the physical properties to the development of commercial devices, the book addresses the applications of WBGS devices for solid-state white-light illumination, medicine and gigahertz-high power telecommunications. In addition, description of recent development in the growth and applications of nitride semiconductors are complemented by chapters on the properties and device applications of SiC, diamond thin films, doping of ZnO, II-IVs and the novel BeZnSeTe/BAlGaAs material systems. Practical issues and problems such as the effect of defects on device performance are highlighted and solutions proposed based on recent studies.
Development and Applications of Wide Bandgap Semiconductors -- Fundamental Properties of Wide Bandgap Semiconductors -- Photonic Devices -- Electronic Devices -- Novel Nano-Heterostructure Materials and Related Devices -- Crystal Growth.
Keywords: Materials science; Solid state physics; Lasers; Photonics; Spectroscopy; Microscopy; Microwaves; Optical engineering; Electronics; Microelectronics; Optical materials; Electronic materials; Materials Science; Optical and Electronic Materials; Solid State Physics; Spectroscopy and Microscopy; Microwaves, RF and Optical Engineering; Laser Technology, Photonics; Electronics and Microelectronics, Instrumentation; Electronic books